Twenty-four-hour profile of peripheral and central blood pressure in young patients with high-normal blood pressure and hypertension - S. B. Silkina; O. N. Antropova; I. V. Osipova (Российский кардиологический журнал)
Aim. To evaluate indicators of daily monitoring of peripheral and central blood pressure in young patients with high-normal blood pressure (HNBP) and essential hypertension (HTN).Material and methods. One hundred twelve patients with HNBP or untreated hypertension aged 25-44 years were included. General clinical investigations were performed. An office blood pressure (BP) were assessed using an automatic BP monitor OMRON M2 Basic. Twenty-four-hour ambulotary BP monitoring (ABPM) on the brachial artery and aorta was carried out for 24 hours using the BpLAB system (OOO Petr Telegin) with an integrated Vasotens system. Depending on BP, patients were divided into groups: with HNBP and hypertension. Statistical processing and comparative analysis of the obtained data were carried out.Results. HNBP group consisted of 47 patients, while the HTN group consisted of 65 patients. The mean age of patients was 34,7±3,2 years. The parameters of daytime and nighttime peripheral BP had significant differences between the HNBP and HTN groups. Aortic BP monitoring revealed following differences: in patients with HTN, central BP values during the day and at night reflected higher values compared to patients from the HNBP group. The number of dippers for peripheral systolic blood pressure (SBP) was more by a quarter (p=0,038) in the HNBP group than in the HTN group. There were no differences in the reduction of diastolic blood pressure (DBP). The reduction in aortic SBP between the groups of HNBP and HTN were comparable. Among hypertensive patients, DBP dippers on the aorta were 20% higher (p=0,04) than in the HNBP group. According to the augmentation and the amplification index reduced to heart rate, there were no significant differences between the groups.Conclusion. Intergroup and intragroup differences were revealed depending on the types of 24-hour profile depending on peripheral and central BP. Reference values and predictive value of central BP require further research.